ANALISIS HUKUM DIVERSITAS DALAM SISTEM PEMBELANJAAN TOTAL - Agung Listiadi, (Pendidikan Ekonomi, 2009)
So that to be an company earn concern going hence needing the existence of rotation of inculcated fund. In this research is used by quantitative descriptive research method By comparing the amount of the maxima hence can know that law of diversitas first have been fulfilled for year 2005 that is that dot of maxima from overall of fund of Rp. 2.610.069.975.893 and this smaller matter than amount of maximum of its elements that is Rp.2.788.420.651.577. So that see that have happened the effort efficient have been done/conducted by PT. Apac Image of Centertex, Tbk in controling permanent nucleus;core fund of him. In the year 2007 also is equal to year 2006 and 2005, law of diversitas first have been fulfilled by that is that dot of maxima from overall of fund that is Rp.2.226.485.457.674 and this smaller matter than amount of maximum of its elements that is Rp.2.788.420.651.577. By comparing both/ second the amount of the minima hence can know that law of diversitas second have been fulfilled, that is dot of minima from overall of fund in the year 2007, 2006 and 2005 successively is Rp. 2.226.485.457.674, 2.325.920.172.002 and 2.610.069.975.893 is bigger than amount of minimum of its elements of Rp. 2.076.400.948.504